Pengaruh Struktur Modal, Ukuran Perusahaan, Profitabilitas Terhadap Nilai Perusahaan (Studi Empiris Perusahaan Manufaktur Terdaftar Di Bursa Efek Indonesia Periode 2010-2013) - Fadilah, Risa Nur Suci, Eko Sugiyanto, M.Si (2016)
The purpose of this research is to examine the significant impact ofCapital Stucture, Company Size and Profitability in Price Book Value at manufacturing companies listed in Bursa Efek Indonesia during 2010-2013. The method of this research is purposive sampling with 36 companies as a sample for every year. This research is done for 2010-2013 period. This research utilizies secondary data. The data are taken from the website Bursa Efek Indonesia (www.idx.co.id). The data which is analyzed in this research are collected through Indonesian Capital Market Directory (ICMD). The data which have already collected are processed with classic assumption test before hypothesis test. Hypothesis test in this research use double regression with t test, F test and coefficient determination test. The result of this research show that partially Capital Stucture, and Company Sizedon't have a significant impact to Price Book Value. Whereas, Profitabilityhave a significant impact to Price Book Value.Capital Stucture, Company Size and Profitability have a significant impact to Price Book Valuesimultaneously.